STUDI TERKAIT DENGAN DAMPAK-DAMPAK KUALITAS LAPORAN KEUANGAN: BUKTI PADA PERUSAHAAN PERBANKAN DI INDONESIA DAN MALAYSIA - Rifaldo Silalahi; Hisar Pangaribuan (Fakultas Ekonomi Universitas Advent Indonesia, 2019)
The purposes of this study are to determine the impact of the quality of financial report on stock trading volume, efficiency of investment and the stock price. This research was conducted upon banking companies listed in the Indonesian Stock Exchange and Malaysian Stock Excahange in 2016 to 2018, with the total sample of 52 companies and the number of sample observation for 3 years, there were156 samples of financial reports. This study used partial least square/ variance based statistical method. The result of this study indicated that the good quality of financial reports, provided additional information on the quality of information for users of financial statements, improved the quality informations for investors, improved the quality of investment decisions, increased stock prices which increased total investment in the investment markets of banking companies in Indonesia and Malaysia. The other result indicated that, the quality of financial report has no significant effect on efficiency of investment.